Altered Structural Correlates of Impulsivity in Adolescents with Internet Gaming Disorder - Du, Xin; Qi, Xin; Yang, Yongxin; Du, Guijin; Gao, Peihong; Zhang, Yang; Qin, Wen; Li, Xiaodong; Zhang, Quan (Frontiers in Human Neuroscience, 2016)
Recent studies suggested that internet gaming disorder (IGD) was associated with impulsivity and structural abnormalities in brain gray matter. However, no morphometric study has examined the association between gray matter and impulsivity in IGD individuals. In this study, 25 adolescents with IGD and 27 healthy controls (HCs) were recruited, and the relationship between Barratt impulsiveness scale-11 (BIS) score and gray matter volume (GMV) was investigated with the voxel-based morphometric (VBM) correlation analysis. Then, the intergroup differences in correlation between BIS score and GMV were tested across all gray matter voxels. Our results showed that the correlations between BIS score and GMV of the right dorsomedial prefrontal cortex, the bilateral insula and the orbitofrontal cortex, the right amygdala and the left fusiform gyrus decreased in the IGD group compared to the HCs. Region-of-interest (ROI) analysis revealed that GMV in all these clusters showed significant positive correlations with BIS score in the HCs, while no significant correlation was found in the IGD group. Our findings demonstrated that dysfunction of these brain areas involved in the behavior inhibition, attention and emotion regulation might contribute to impulse control problems in IGD adolescents.